PENINGKATAN SELF EFFICACY MAHASISWA MELALUI PENGGUNAAN MODUL FISIKA BERBASIS KONSEP (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
Students' confidence in their ability to study material and work on physics questions needs to be a concern during the covid-19 pandemic. This belief is called self-efficacy. This self-efficacy can be increased by using teaching materials that are designed by educators according to the characteristics of the students they teach. Concept-based modules are used in basic physics lectures on Particle Dynamics. This study aims to describe the increase in student self-efficacy before and after using the module. In addition, this study also wanted to see whether there was a significant difference in student self-efficacy between before and after using the module. This research method uses a pre-experimental method with one group pretest posttest design. The sample used in the research is odd semester students for the 2021/2022 academic year. The results showed the <N-Gain> value of 0.45 which indicated that there was an increase in student self-efficacy after using the concept-based module in the moderate category. The difference in student self-efficacy between before and after using the concept-based module was also significant by referring to the sig value. (2-tailed) 0.000 < 0.05.